2009
DOI: 10.1111/j.1600-051x.2009.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in periodontitis during pregnancy and the risk of pre‐term birth and low birthweight

Abstract: Aim-Determine if periodontitis progression during pregnancy is associated with adverse birth outcomes.Materials and Methods-We used clinical data and birth outcomes from the OPT Study, which randomized women to receive periodontal treatment before 21 weeks gestation (N=413) or after delivery (410). Birth outcomes were available for 812 women and follow-up periodontal data for 722, including 75 whose pregnancies ended <37 weeks. Periodontitis progression was defined as ≥ 3mm loss of clinical attachment. Birth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
4
43
0
5
Order By: Relevance
“…To date, only a few authors have investigated the association between periodontitis and very low birthweight pre-term delivery (£32 weeks and £1500 g) [39,40]. Our results are consistent with previous studies that found no significant association between periodontitis and the risk for pre-term birth at <37 weeks [39,40].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…To date, only a few authors have investigated the association between periodontitis and very low birthweight pre-term delivery (£32 weeks and £1500 g) [39,40]. Our results are consistent with previous studies that found no significant association between periodontitis and the risk for pre-term birth at <37 weeks [39,40].…”
Section: Discussionsupporting
confidence: 95%
“…Our results are consistent with previous studies that found no significant association between periodontitis and the risk for pre-term birth at <37 weeks [39,40]. We also found no evidence that periodontal disease increases very pre-term birth risk of women (£32 weeks), as reported by Michalowicz et al [40], whereas Offenbacher et al [39] reported a positive relation between periodontitis and very pre-term birth (£32 weeks).…”
Section: Discussionsupporting
confidence: 94%
“…The association between periodontitis and gestational complications, such as low birth weight (LBW), has been investigated widely for almost 2 decades, but there is still no consensus view 6–12 . The justification for this lack of consensus relates to other determinants that affect LBW and hence may camouflage the relationship with periodontitis.…”
mentioning
confidence: 99%
“…It has been hypothesized that systemic inflammation, attributable to periodontal infection and bacterial colonization in the absence of adequate maternal antibody responses to specific periodontal pathogens, might contribute to such adverse outcomes. Notably, other studies have failed to reproduce the associations between periodontal diseases and pregnancy outcomes 8‐13 . Furthermore, although some studies 14,15 have shown that treatment of periodontal disease during pregnancy is of benefit to birth outcomes, 16 others have failed to show such an effect 17‐19 …”
mentioning
confidence: 99%